2004
DOI: 10.1002/elps.200406026
|View full text |Cite
|
Sign up to set email alerts
|

Critical aspects of analysis of Micrococcus luteus, Neisseria cinerea, and Pseudomonas fluorescens by means of capillary electrophoresis

Abstract: Within the frame of our study we investigated Microccocus luteus, Neisseria cinerea, and Pseudomonas fluorescens by means of capillary zone electrophoresis (CZE). They form chains and clusters on a different scale, which can be reflected in the electropherograms. A low buffer concentration of Tris-borate and Na2EDTA containing a polymeric matrix of 0.0125% poly(ethylene) oxide (PEO) was used. Key factors were the standardization and optimization of CE conditions, buffer solution, and pretreatment of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Although CE represents a promising approach for such microbial separations, it is essentially a phenotypic approach and therefore may suffer from certain limitations as a diagnostic method. For example, pleiomorphic or chain-forming cells may not be resolved adequately via CE, due to the wide range of cell surface charge values occurring within these populations [4,13]. Conversely, it may be difficult to separate closely related cell types, such as Salmonella Typhimurium and Escherichia coli due to their physiological similarities.…”
Section: Introductionmentioning
confidence: 94%
“…Although CE represents a promising approach for such microbial separations, it is essentially a phenotypic approach and therefore may suffer from certain limitations as a diagnostic method. For example, pleiomorphic or chain-forming cells may not be resolved adequately via CE, due to the wide range of cell surface charge values occurring within these populations [4,13]. Conversely, it may be difficult to separate closely related cell types, such as Salmonella Typhimurium and Escherichia coli due to their physiological similarities.…”
Section: Introductionmentioning
confidence: 94%
“…The latter was reported as depending on the bacteria species, the applied voltage, the buffer composition, the injection volume and the cell concentration [18,20]. Buffer and sample composition (cell concentration, matrix components in real samples) [15,16,18,[24][25][26], bacteria growth phase [27] and storage conditions [27] were factors that influenced peak shapes and migration times. Migration time shifts were also observed when mixtures of bacteria species had been injected [18,28].…”
Section: Introductionmentioning
confidence: 99%
“…In successive years, several laboratories directed their studies toward the analysis of microorganisms with interest in food industry, clinical diagnosis and environmental control, using diluted polymer-based BGEs [44][45][46][47][48][49][50]. Shintani et al [44] successfully detected Salmonella enteritidis, the causative agent of a major foodborne disease, by CE and the aid of UV and LIF detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the reproducibility of the CE patterns obtained from the analysis of microorganisms by this strategy seems to be largely affected by variables such as BGE ionic strength, as well as by pretreatment, physiological state and storage conditions of cells [46]. In addition, Hoerr et al [47] reported that such susceptibility of the separation system to small experimental conditions variations also depends on the microorganisms under study. The diluted PEO-based BGE also proved to be invaluable for the rapid identification and quantitation of Edwardsiella tarda, a pathogen of commercially important fish [48].…”
Section: Introductionmentioning
confidence: 99%